Health Inequities Exist in Europe: Are Spatial Health Inequities Present in the Small State of Malta?. (February 2022) - Cuschieri, Sarah; Calleja, Neville; Mamo, Julian
Targeting and reducing health inequities is a requisite for public health. The Maltese Islands are divided into six geographical districts with a total area of 316 km 2 . It is anticipated that the close geographical proximity and social integration would result in similar population health status. This study aims to identify whether geographical health inequities exist despite the small country area. A cross-sectional health examination survey was conducted. Participants with type 2 diabetes (T2DM) and impaired fasting blood glucose (IFG) were identified, depending on their medical and drug history and fasting blood glucose levels. Those with body mass index ≥30 kg/m 2 were labeled as obese. Different health status was compared between the residents in the different districts according to demographic, socioeconomic, lifestyle, and medical history. Regression analysis was carried out to identify links between the different districts, BMI, IFG, and T2DM diagnosis, while adjusting for confounders. Geographical inequities were evident despite the close proximity. The Gozo district exhibited distinctive metabolic inequities compared to the other districts. An independent relationship was present between IFG diagnosis and residence in Gozo and Northern districts. Obesity was linked to residing in Gozo. Health inequities were evident between the close districts of the Maltese Islands despite similar socioeconomic, lifestyle, and healthcare provision. Psychosocial factors might be the underlying causes for these inequities. Public health officials and government should work to enhance public education and set up local policies and interventions to target these inequities.